Dynamical approach for positive solutions of semilinear elliptic problems in unbounded domains - Berestycki, H.; Efendiev, M.; Zelik, S. (Нелинейные граничные задачи, 2004)
We apply the trajectory dynamical systems approach to study the positive solutions of a semilinear elliptic problem in an unbounded domain tt. The existence of the global attractor for the trajectory dynamical system associated with this problem is proved. The symmetrization and stabilization properties of positive solutions as |x| → ∞ oo are also established in three dimensional case Ω ⊂ R³.